Proyecto de inversión para la mejora en el servicio postal público del Ecuador en Guayaquil - Carrera Bosquez, Mariela Alexandra (2009)
The present thesis is developed on the basis of the problems presented by the Ecuadorian Public Postal Service, Post office of Ecuador (CDE) in Guayaquil and, the improvement of their logistic process, focusing mainly in the delay of the send and delivery of charges at local and international level. The causes of the inefficiency of the public company have been analyzed according to: 5. The changes in the legal-organizational status of the company; 5. The evaluation in the position of market of this company; 5. The degree of effectiveness especially in the quality levels in the benefit of the service. By a market study it was determined in addition, which is the present reality of CDE against its competitors and their consequences, which force to improve the quality of its postal services concentrating in five of the total of the same, because they have greater demand in the market, and that when improving them will represent an increase in their gains and market participation in a 2%. It was evaluated in addition, the behavior of VAN and the TIR that in a preservative scene was of $ 13,954, 57 and 13,85% respectively, which indicates that our project is profitable, because in the comparison between two projects or two alternatives of a same project, the best one, in principle, is that one with major VAN The total investment of the project will be assumed by Post office of Ecuador, whose amount is of $ 65,059, 38 which recover in four years and seven months once implemented the project, according to the Financial Study